Mujer y nación: una historia de la educación en Baja California. 1920-1930 - María del Consuelo López Arámburo (El Colegio de la Frontera Norte, 2005)
This article forms part of research in progress that aims to examine the intellectual climate prevailing in Mexico in the post-revolutionary period, from 1920 to 1930. The essay explores how the influence of nationalist ideology gradually shifted the role of Mexican women, identifying them as the educators of the nation. The study focuses on Baja California since educators, such as Josefina Rendón Parra (1885-1977), were an important example illustrating how nationalist ideology engineered women´s role in Mexico´s reconstruction. Education with a spiritual dimension was the key doorway through which women gained access to the modern era. In a society that had yet to grant them the right to vote, education was also the doorway through which women gained acceptance as citizens. Finally, this study proposes the remaking of history through the mythological discourses, such as the legends that were fashionable in that period.